India As a Democratic Nation- Concepts and Perceptive - Gayatri Sunkad (Green Publisher Indonesia, 2024)
India, as the world's largest democracy, presents a unique and diverse political landscape. Since gaining independence in 1947, it has upheld democratic ideals amidst challenges of diversity, inequality, and external threats. This paper explores the foundational concepts of Indian democracy, its key features, and its role as a beacon of democratic governance in the global arena. By examining India’s electoral system, constitutional framework, and challenges, we gain insights into how democracy functions in one of the most populous and complex nations in the world.